Analysis of different standards for life support technology in manned submersible - Jiang, Lei; Ye, Cong; Li, Hongxia; Wang, Yao; Jiang, Nian (Frontiers in Physiology, 2024)
Life support technology is one of the most critical technologies of manned submersibles, which acts on the pilots of the submersible, thus directly affecting the underwater safety of manned submersibles. Due to the importance of life support technology, many countries or international organizations have put forward some standards or specifications for life support technology. This paper presents an overview of the life support technology of manned submersibles. It compares the standards related to life support technology proposed by different countries or organizations. Furthermore, it analyzes the specific data of oxygen supply and carbon dioxide absorption, both of which are critical aspects of life support technology in each standard. It also selects the data that is widely acknowledged and recognized as the basis for the establishment of ISO standard (ISO 22252:2020). Finally, these ISO standard data such as oxygen concentration and carbon dioxide concentration are further confirmed by the environmental parameters of manned submersibles such as "Fendouzhe".